Sistem Informasi Pemeteaan Kesehatan Ibu dan Anak Untuk Menekan Angka Kematian Pada Bayi - , (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2019)
With the status of the new administrative area there are still not many basic infrastructure supporting the community. These basic facilities such as health facilities, educational facilities, population service facilities and others. The facilities most needed by the community are health facilities. From the data of the Kediri district health office in 2016 the health facilities in the district of Badas, such as puskesmas, polindes and posyandu. While health personnel are general practitioners, there are 1 person, 1 dentist, 5 nurses, 1 pharmacy staff, 1 nutritionist and 1 health analyst. By using the Georgrafis Information System (GIS) approach to determine the spatial distribution of maternal and child health in Badas Subdistrict, Kediri Regency, carried out an analysis to create an information system for mapping maternal and child health. GIS describes spatial distribution of maternal and child health, the characteristics of regions prone to spatial maternal and child health and information for mapping maternal and child health. This system can be used as a means to obtain the latest sources of information, namely mapping of maternal and child health and regular information on the development and advancement of technology-based maternal and child health and as input for information to be taken into consideration in making policies related to budget allocation, recruitment and placement of resources Human (HR), especially in the health sector.